2021
DOI: 10.3389/fpsyg.2021.558044
|View full text |Cite
|
Sign up to set email alerts
|

Keep Calm and Carry On: The Relations Between Narrative Coherence, Trauma, Social Support, Psychological Well-Being, and Cortisol Responses

Abstract: In order to explain trauma resilience, previous research has been investigating possible risk and protective factors, both on an individual and a contextual level. In this experimental study, we examined narrative coherence and social support in relation to trauma resilience. Participants were asked to write about a turning point memory, after which they did the Maastricht Acute Stress Test, our lab analog of a traumatic event. Following, half of the participants received social support, whereas the other half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…However, if they experienced family-related trauma, their narrative identity looped, becoming an iterated trauma story with a singular self-image of a hero or a victim. Vankeen et al [ 12 ] show that narratives of traumatic experiences were less coherent, reflected unfinished attempts at meaning-making, and shared similarities with continuous rumination. Thus, perseveration of narrative threads by people with dementia is not just a symptom of cognitive impairment [ 63 ] but may also mark a non-adaptive form of coping with important life-events of a possible traumatic background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if they experienced family-related trauma, their narrative identity looped, becoming an iterated trauma story with a singular self-image of a hero or a victim. Vankeen et al [ 12 ] show that narratives of traumatic experiences were less coherent, reflected unfinished attempts at meaning-making, and shared similarities with continuous rumination. Thus, perseveration of narrative threads by people with dementia is not just a symptom of cognitive impairment [ 63 ] but may also mark a non-adaptive form of coping with important life-events of a possible traumatic background.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating the meaning of stressful experiences also impacts our ability to cope with stress and can slow or accelerate biological aging [ 5 ]. Therefore, recently the function of narrative identities has been studied in the context of living with chronic somatic diseases, such as endometriosis [ 6 ], HIV [ 7 ] or cancer [ 8 ], and coping with various types of mental disorders like mood disorders [ 9 ], bipolar disorder [ 10 ], psychosis spectrum [ 11 ], PTSD [ 12 ], and borderline personality [ 13 ]. To the best of our knowledge, the narrative identities of people with dementia have been studied far too rarely [ 14 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…When we frame our lives in a way that revolves around a traumatic experience, the accompanying feelings and stress caused by the event have affect us long after the traumatic event. In cases of post-traumatic stress disorder, stored information about the personal narrative can be very dangerous and affect the entire structure of the narrative (Vanaken et al, 2021).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Alternatively, the narrative style and language that individuals use when recounting traumatic events have been suggested to provide deep insights into their mental well-being [42][43][44]. Research has shown that the way in which individuals remember and describe traumatic events, encompassing the language used in the narrative, is connected to the expression of their post-traumatic stress symptoms [45].…”
Section: Introductionmentioning
confidence: 99%